A Multicenter Study of the Causes and Consequences of Optimistic Expectations About Prognosis by Surrogate Decision-Makers in ICUs*. Issue 9 (September 2019) - White, Douglas B.; Carson, Shannon; Anderson, Wendy; Steingrub, Jay; Bird, Garrett; Curtis, J. Randall; Matthay, Michael; Peterson, Michael; Buddadhumaruk, Praewpannarai; Shields, Anne-Marie; Ernecoff, Natalie; Shotsberger, Kaitlin; et al.
Abstract : Objectives: Optimistic expectations about prognosis by surrogate decision-makers in ICUs are common, but there are few data about the causes and clinical consequences. Our objective was to determine the causes of optimistic expectations about prognosis among surrogates and whether it is associated with more use of life support at the end of life. Design: Prospective, multicenter cohort study from 2009 to 2012. Setting: Twelve ICUs from multiple regions of the United States. Subjects: The surrogates and physicians of 275 incapacitated ICU patients at high risk of death. Interventions: None. Measurements and Main Results: Surrogates and physicians completed a validated instrument assessing their prognostic expectations for hospital survival. We determined the proportion of surrogates with optimistic expectations, defined as a prognostic estimate that was at least 20% more optimistic than the physician's, then determined how frequently this arose from surrogates miscomprehending the physicians' prognosis versus holding more hopeful beliefs compared with the physician. We used multivariable regression to examine whether optimistic expectations were associated with length of stay, stratified by survival status, and time to withdrawal of life support among nonsurvivors. Overall, 45% of surrogates (95% CI, 38–51%) held optimistic expectations about prognosis, which arose from a combination of misunderstanding the physician's prognostic expectations and from holding more hopeful beliefs compared with the physician. Optimistic expectations by surrogates were associated with significantly longer duration of ICU treatment among nonsurvivors before death (β coefficient = 0.44; 95% CI, 0.05–0.83; p = 0.027), corresponding to a 56% longer ICU stay. This difference was associated with a significantly longer time to withdrawal of life support among dying patients whose surrogates had optimistic prognostic expectations compared with those who did not (β coefficient = 0.61; 95% CI, 0.16–1.07; p = 0.009). Conclusions: The prevalent optimism about prognosis among surrogates in ICUs arises both from surrogates' miscomprehension of physicians' prognostications and from surrogates holding more hopeful beliefs. This optimism is associated with longer duration of life support at the end of life. Abstract : Supplemental Digital Content is available in the text.